Short Term Outcome of Image Guided (USG) Percutaneous Pigtail Catheter Drainage of Intra-abdominal Abscess (Bangladesh Medical Journal, 2025)
In surgical practice, it is common and important to deal with intra-abdominal abscesses. Incision and drainage through laparotomy has traditionally been used to manage abdominal abscesses. Percutaneous catheter drainage is favorable due to avoiding of laparotomy, general anesthesia, easier postoperative care, less patients’ complaints, shortened hospital stay and less cost. However, the advance technology of ultrasonography helps for precise localization of abscesses to place the catheter percutaneous for effective, adequate and definitive drainage. This hospital based prospective observational study was carried out among the patients of intra-abdominal abscess and the aim was to measure the short-term outcomes of drainage of intra-abdominal abscesses with an image-guided percutaneous pigtail catheter. Study subjects were selected from patients with intra-abdominal abscess and were enrolled as per selection criteria. Data connected to intra-abdominal abscess derived from the pan-procedure was collected on or after the follow-up sheet and also from post-procedure investigation reports. The questionnaire was finalized following pretesting. Collected data were checked daily and edited (if needed). Data were processed and analyzed using computer software SPSS (Statistical Package for Social Sciences) version 20. Quantitative data were expressed as mean and standard deviation. Qualitative data were expressed as frequency and percentage; and comparison was done by fisher exact test. A probability value (p) of less than 0.05 was considered as statistical significance. This study finds that maximum patients (30%) were in the age group of 41-50 years and males were predominant (65%). Most of the (85%) pig-tail catheters were used for intra-abdominal abscess were 14Fr size. All most all (95%) of the intra-abdominal abscess were single abscess and a few of those (5%) were multiple abscess. More than half (55%) of the abscess were appendicular, 10% were liver abscess, one-fourth (25%) of those were sub-hepatic and 10% were sub phrenic abscess. It was observed that 95% required single drainage and 5% required multiple drainage. All most all of the patients (95%) were given local anesthesia and only 1 patient (5%) needed conversion (open surgery). Nearly two-third (65%) patients were needed hospital stay for 6 to 10 days. Most of them (90%) were success and failures were minimum (10%). The average (Mean ± SD) catheter removal was 6.90±1.87 days and most of the patients (90%) had no complications. It was observed that 60% organism were escherchia coli, 25% were staph. aureus, 5% were pseudomonas and 10% were streptococcus spp. Using an image-guided percutaneous pigtail catheter for drainage of intra-abdominal abscesses is easily applicable, well-tolerated procedure that doesn't require general anesthesia with high success rates and low complications. The practice of this method can reform the treatment policy for drainage of intra-abdominal abscesses.Bangladesh Med J. 2024 Jan; 53(1): 1-6